2021
DOI: 10.1186/s12893-021-01363-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of lymph node dissection in intrahepatic cholangiocarcinoma: a multicenter retrospective study

Abstract: Background Lymph node dissection (LND) is of great significance in intrahepatic cholangiocarcinoma (ICC). Although the National Comprehensive Cancer Network (NCCN) guidelines recommend routine LND in ICC, the effects of LND remains controversial. This study aimed to explore the role of LND and some related issues and of in ICC. Methods Patients were identified in two Chinese academic centers. Inverse probability of treatment weighting (IPTW) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The Z0011 study demonstrated that additional axillary nodal dissection after sentinel node biopsy does not improve prognosis in patients with breast cancer (28)(29)(30). Similarly, in many carcinomas, lymph node metastasis is thought to be important for accurate staging, but prophylactic nodal dissection does not improve prognosis (31)(32)(33)(34)(35). In contrast, the therapeutic effect of prophylactic lymph node dissection in patients with gastric cancer has been verified.…”
Section: Characteristics Of Lymph Node Metastasis In Patients With Gastric Cancermentioning
confidence: 99%
“…The Z0011 study demonstrated that additional axillary nodal dissection after sentinel node biopsy does not improve prognosis in patients with breast cancer (28)(29)(30). Similarly, in many carcinomas, lymph node metastasis is thought to be important for accurate staging, but prophylactic nodal dissection does not improve prognosis (31)(32)(33)(34)(35). In contrast, the therapeutic effect of prophylactic lymph node dissection in patients with gastric cancer has been verified.…”
Section: Characteristics Of Lymph Node Metastasis In Patients With Gastric Cancermentioning
confidence: 99%
“…Intrahepatic cholangiocarcinoma (ICC) is a rare and fatal disease [ 2 , 5 ], and lymph node metastasis associated with this condition is an independent risk factor that affects the prognosis of ICC patients [ 20 ], and the choice of surgical methods for treatment [ 21 ]. The vast majority of related studies in this realm used logistic regression to screen risk factors and then established nomograms to try to predict lymph node metastasis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the future, if the sample size can be expanded and data from large scale international centers can be included, our machine learning method can be improved to make more accurate predictions. Previous studies have shown that ICC patients with lymph node metastases tend to have poor survival rates [ 7 , 20 ]. However, due to a lack of follow-up data, a detailed survival analysis of predicted patients could not be performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…recommended that at least lymph node stations 8 and 12 should be dissected irrespective of the tumor location. Although LND is effective for evaluation of nodal status, studies are becoming increasingly skeptical about the benefits of LND for prognostication ( 33 35 ). To date, routine LND remains controversial; however, a multi-center study shows that selected patients with iCCA could benefit from LND ( 36 ).…”
Section: Discussionmentioning
confidence: 99%